Diuraphis noxia (Hemiptera: Aphididae): Identificación de los biotipos presentes en poblaciones argentinas - Ricci, Elisabet Mónica (2012)
The aim of the current research was to assess the plant responses of wheat lines and differential cultivars carrying Diuraphis noxia Kurdjumov resistance genes when subjected to aphid infestation, in order to determine the biotypic composition of RWA populations in Argentina. Eighteen lines and differential cultivars were sown in a greenhouse in a randomized design with two replicates. Two recordings of the chlorotic damage and the level of leaf rolling were made after 21 and 51 days from the infestation onset. The results were analyzed with an ANOVA and Tuckey Test (=0.05). After 21 days of infestation, two novel lines (14 and 1) showed the highest level of tolerance, with minor chlorotic damage. The differential cultivars carrying Dn2 and Dn7 resistance genes also were highly tolerant, Dn1 and dn3 resistance genes were moderately tolerant and those ones carrying Dn4 and Dn5 genes resulted seriously damaged. After 51 days of infestation, only the differential cultivar carrying Dn7 and the novel lines 14 and 1 maintained a high level of tolerance. Based on the current results, the RWA biotypes 1, 2* and 5* are present in Argentina, the last ones with different characteristics from biotypes 2 and 5 identified in EEUU. We conclude that improved cultivars in other countries can behave as susceptible against local populations.